(3GdTgH GddGeYI aj GdSjGSI GdfGaYIs - (3YHO Gddg Hf jhSa Hf QVhGf GdfLGQj GdeGdbj, CHh GdbGSe , J (B782 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPi OHQ HMceJg GdHGdZI CehQ YHGOg CeG HYO aCf ebGe GdNdGaI GdYdjI GdJi HSWgG Gddg Ydi GdHSjWI s
(3BNQgG (B:s
(3Ef MRH Gddg ge GdZGdHhf fLR HMeO Gddg s
(3HgG WeS TOjOs
(3fSNI KGfjIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3QVhGf ecfGS (B- (3GdeZQH (B(5) s
Keywords: (3GdSjGSI hGdGLJeGYs